2022
DOI: 10.1002/pan3.10401
|View full text |Cite
|
Sign up to set email alerts
|

Local ecological knowledge provides novel evidence on threats and declines for the Caucasian grouse Lyrurus mlokosiewiczi in Arasbaran Biosphere Reserve, Iran

Abstract: 1. The Caucasian grouse Lyrurus mlokosiewiczi, one of the most poorly known species of grouse, is experiencing population declines associated with multiple threats. Evaluating species' population status in relation to different local human activities is important to inform conservation and identify suitable management methods, but determining status and threats for poorly known taxa may require assessment of non-standard sources of ecological information. 2. We investigated what novel insights can be provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Several informants reported that there used to be more lorises or that there are fewer individuals now that the town, village, and market areas are no longer forested. This finding tracks with our understanding that local people appear to be sensitive to population declines and often link them either overtly or covertly to a rationale [17,67,68]. Local people appeared to link loris population declines covertly with electrocution.…”
Section: Discussionsupporting
confidence: 75%
“…Several informants reported that there used to be more lorises or that there are fewer individuals now that the town, village, and market areas are no longer forested. This finding tracks with our understanding that local people appear to be sensitive to population declines and often link them either overtly or covertly to a rationale [17,67,68]. Local people appeared to link loris population declines covertly with electrocution.…”
Section: Discussionsupporting
confidence: 75%
“…These villages are located in the West, North and East of Ebo forest while the Southern part is largely covered by Forest Management Unit (07-002) with no human habitations close to the forest. Methods for collecting data on local ecological knowledge typically involve interviews through which investigators obtain information directly from interviewees or key participants, using either questionnaires containing predefined questions or informal conversations (Camino et al 2020;Ghanbari and Turvey 2022). Because most of the villages around the Ebo forest have few habitations (per.…”
Section: Data Collectionmentioning
confidence: 99%
“…Little is documented on local knowledge on A. preussi in the Ebo forest (Whytock et al 2021), yet such knowledge may be important for their conservation. Local knowledge, with growing interest in its role, scope, and value, represents a supporting complementary information for the conservation of bio- diversity (Ghanbari and Turvey 2022;IPBES 2019;Turvey et al 2014;Zayonc and Coomes 2022). The Ebo forest which represents the most important tract of intact forest landscape in the Cross-Sanaga-Bioko coastal forest ecoregion (Potapov et al 2017) is one of A. preussi strongholds in Cameroon.…”
Section: Introductionmentioning
confidence: 99%
“…According to the De Marton classification, Arasbaran Forests have a Mediterranean climate [25]. The limestone and igneous are the two dominant lithology units that geologically belong to the third period [25,26].…”
Section: Study Areamentioning
confidence: 99%